A critique on the investigation and adjudication powers of the Fair Competition Commission and finality clause of the Fair Competition Tribunal in Tanzania: a reflection from Jamaican and South African competition law - Prosper, Edward Kisioki (Department of Commercial Law, 2014)
Includes bibliographical references.